Fungal Spinal Osteomyelitis in the Immunocompromised Patient: MR Findings in Three Cases - Williams, Robert L.; Fukui, Melanie B.; Cidis Meltzer, Carolyn; Swarnkar, Amar; Johnson, David W.; Welch, William (American Journal of Neuroradiology, 1999)
Summary: The MR imaging findings of fungal spinal osteomyelitis in three recipients of organ transplants showed hypointensity of the vertebral bodies on T1-weighted sequences in all cases. Signal changes and enhancement extended into the posterior elements in two cases. Multiple-level disease was present in two cases (with a total of five intervertebral disks involved in three cases). All cases lacked hyperintensity within the disks on T2-weighted images. In addition, the intranuclear cleft was preserved in four of five affected disks at initial MR imaging. MR features in Candida and Aspergillus spondylitis that are distinct from pyogenic osteomyelitis include absence of disk hyperintensity and preservation of the intranuclear cleft on T2-weighted images. Prompt recognition of these findings may avoid delay in establishing a diagnosis and instituting treatment of opportunistic osteomyelitis in the immunocompromised patient.